Analysis of the Contribution of Bantimurung Bulusaraung Nature Tourism Park to the Original Regional Income (PAD) of Maros Regency - Rinaldi, Rinaldi; Hema, Poramet (Multidisciplinary Journal of Tourism, Hospitality, Sport and Physical Education, 2024)
Purpose of the study: This study aims to examine the contribution of Bantimurung Nature Tourism Park to the Regional Original Income of Maros Regency, identify PAD sources, and evaluate the application of public sector accounting science in the context of this contribution in society. Methodology: This study uses a qualitative approach. The focus of this study is how the Bantimurung Tourism Park Contribution to the Original Regional Income of Maros Regency and the factors that encourage and inhibit the potential of Bantimurung natural tourism objects. The data sources used in this study are interviews and documents at the Maros Regency Culture and Tourism Office. Main Findings: The results of the study show that the Original Regional Income (PAD) of Maros Regency increased from 2016 to 2019, but decreased in 2020 due to the COVID-19 pandemic. The contribution of Bantimurung Nature Tourism Park to PAD was highest in 2016 at 4.49%, but decreased to 1.95% in 2020. This decrease was caused by social restrictions which drastically reduced the number of tourists. The contribution of Bantimurung Park greatly affects Maros. Novelty/Originality of this study: This study analyzes the impact of the COVID-19 pandemic on the contribution of the Bantimurung Bulu Saraung Tourism Park to the PAD of Maros Regency, including the influence of the PSBB policy on tourist visits and regional income. This study also fills the gap in regional tourism literature, evaluates the role of nature tourism in the economy, and offers crisis mitigation strategies, based on empirical data from 2016-2020.